Pengaruh Persepsi Kemudahan Penggunaan, Manfaat, dan Keamanan terhadap Loyalitas Pengguna Mobile Banking dengan Minat dan Kepuasan Pengguna sebagai Variabel Mediasi - Shafira Meiza Paradisha; Amelia Setiawan; Hamfri Djajadikerta (BADAN PENERBIT STIEPARI PRESS, 2025)
The launch of the Coretax system by the Directorate General of Taxes (DGT) represents a significant step in Indonesia's tax modernization, aiming to streamline administration and boost efficiency. However, its initial implementation faced severe technical issues, leading to substantial disruptions. This study analyzes the challenges encountered, evaluates stakeholder responses (government, businesses, consultants), identifies the causes of technical failures, and assesses the impact on business operations, tax revenue, and compliance. Using qualitative content analysis, 66 news summaries from Indonesian online media between November 2024 and March 2025 were examined. Findings indicate that widespread technical issues, such as errors and access difficulties, significantly burdened users and generated complaints. The government’s response was mainly reactive, offering penalty removals and commitments for system improvements. Issues also extended to governance, external oversight by institutions like DPR and KPK, and concerns over fiscal implications. The study identifies key factors contributing to the challenges, including inadequate system readiness, poor socialization, and lack of thorough pre-implementation testing. It underscores the complexity of large-scale public sector digitalization in Indonesia, calling for urgent improvements in planning, testing, governance, and stakeholder involvement for the successful implementation of Coretax and future digital initiatives.